What are the barriers to, and enablers of, working with people with lived experience of mental illness amongst community and voluntary sector organisations? A qualitative study - Baxter, Louise (PLoS One, 2020)
There is increasing emphasis on psychological and social approaches to managing and treating mental illness, including a growing evidence base on the effectiveness of community-based social interventions including arts and heritage activities, library programmes, volunteering schemes, nature-based activities and community groups. However, there is a gap in understanding of what the barriers to, and enablers of, working with individuals with mental illness might be for the community and voluntary sector. A qualitative approach was used involving focus groups with non-profit organisations delivering social activities within communities across the United Kingdom. Behaviour Change Theory, the COM-B model and the Theoretical Domains Framework, were employed as the theoretical framework, to develop interventions to address the barriers raised. Representatives of the organisations reported being motivated by the mental health needs of others, and by seeing the benefits of participation. Further motivations included expanding inclusion, and economic motivation to ensure sustainability. Strengths identified included offering innovative, responsive services that were distinct from conventional mental health services. Running these services demanded new and potentially challenging skills, such as understanding statutory responsibilities, and being able to train and support staff. Further challenges included maintaining boundaries between their roles as community organisations and clients’ mental health needs and avoiding burn-out. Ability to deliver this work was enhanced by support of peer organisations and opportunities to share practice. However, funding was often short term, and complex to obtain, which could destabilise organisations’ sustainability. Lack of transparency around the process, differences in language between the community and health sectors, and confusion around commissioning pathways undermined the potential opportunity offered by social prescribing policy. Interventions to address these barriers were identified, including long term funding to support core costs, training on engaging with the commissioning process, around mental health support and safeguarding, and developing mentoring schemes and local co-operatives of organisations for developing partnerships with the health sector.